Establishment and outcomes of a model primary care pharmacy service system. - Carmichael JM; Alvarez A; Chaput R; Jennifer Dimaggio R; Magallon H; Mambourg S (American Journal of Health-System Pharmacy, 2004)
The establishment and outcomes of a model primary care pharmacy service system are described. A primary care pharmacy practice model was established at a government health care facility in March 1996. The original objective was to establish a primary pharmacy practice model that would demonstrate improved patient outcomes and maximize the pharmacist's contributions to drug therapy. Since its inception, many improvements have been realized and supported by advanced computer and automated systems, expanded disease state management practices, and unique practitioner and administrative support. Many outcomes studies have been performed on the pharmacist-initiated and -managed clinics, leading to improved patient care and conveying the quality-conscious and cost-effective role pharmacists can play as independent practitioners in this environment. These activities demonstrate cutting-edge leadership in health-system pharmacy. Redesign has been used to improve consistent access to a medication expert and has significantly improved the quality of patient care while easing physicians' workload without increasing health care costs. A system using pharmacists as independent practitioners to promote primary care has achieved high-quality and cost-effective patient care.